2022
DOI: 10.13057/biodiv/d230551
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal analysis of dholes (Cuon alpinus) in Khao Yai National Park, Thailand

Abstract: Abstract. Khoewsree N, Pla-ard M, Sukmasuang R, Paansri P, Chanachai Y, Kaewdee B, Phengthong P. 2022. Spatio-temporal analysis of dholes (Cuon alpinus) in Khao Yai National Park, Thailand. Biodiversitas 23: 2668-2678. The relationship of the occurrence of key wildlife species and other wildlife in the ecosystems is complex and unique as a result of interactions between species as well as responses to complex environments. Spatio-temporal analysis of dholes (Cuon alpinus) in Khao Yai National Park, Thailand, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…According to Su et al (2022), all of the carnivorous species mentioned have the potential to prey on grounddwelling birds, including pheasants. Khoewsree et al (2022) reported a significant spatial and temporal overlap between the RJF and SFB with Dhole in Khao Yai National Park. Similarly, Charaspet et al (2021) found that the presence of RJF corresponds to the niche overlap index of carnivorous mammals when considering spatial and temporal overlap coefficients in Huai Kha Khaeng Wildlife Sanctuary (HKKWS).…”
Section: Discussionmentioning
confidence: 92%
“…According to Su et al (2022), all of the carnivorous species mentioned have the potential to prey on grounddwelling birds, including pheasants. Khoewsree et al (2022) reported a significant spatial and temporal overlap between the RJF and SFB with Dhole in Khao Yai National Park. Similarly, Charaspet et al (2021) found that the presence of RJF corresponds to the niche overlap index of carnivorous mammals when considering spatial and temporal overlap coefficients in Huai Kha Khaeng Wildlife Sanctuary (HKKWS).…”
Section: Discussionmentioning
confidence: 92%
“…Managers of Khao Yai National Park are challenged with reducing the impacts of human disturbance on wildlife, especially for the pheasant family and terrestrial birds (Jameel et al 2022), which are most active during the day, the same as a human activity. Khoewsree et al (2022) reported that humans, comprising tourists and some groups of villagers who go into the area illegally, also significantly coexisted temporally and spatially with wildlife in KYNP.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the Variable squirrel (Callosciurus finlaysonii) and Grey-bellied squirrel (Callosciurus caniceps) that were found occasionally in the area outside of the study plot, these animals were not captured during the study period and this may be due to that species requiring a different habitat. Other factors would be that cages were placed at ground level and there was an abundance of carnivores in the area (Khoewsree et al 2020(Khoewsree et al , 2022. Determination of the order and the family levels revealed that all numbers of the order and family levels were more likely to be found in the dry evergreen forest than in disturbed areas.…”
Section: Discussionmentioning
confidence: 99%